Case Report: CytoSorb hemoadsorption as an adjunctive therapy in critically ill pregnant women with COVID-19 and acute kidney injury—a case series - Almasi, Minoo Heidari; Miri, Mir Mohammad; Entezarmahdi, Kiana; Sabaghian, Tahereh; Sadeghi, Soheila; Nassiri, Amirahmad (Frontiers in Medicine, 2025)
PurposeCritically ill pregnant women with COVID-19 are at high risk for acute kidney injury (AKI) and a hyperinflammatory state, contributing to multiorgan failure. This case series describes the adjunctive use of CytoSorb hemoadsorption therapy in this population.MethodsWe present four critically ill pregnant women with COVID-19 pneumonia, AKI, and clinical signs of hyperinflammation. All patients were admitted to the intensive care unit (ICU) and received CytoSorb therapy, integrated with continuous renal replacement therapy (CRRT) or used as a standalone treatment. We analyzed clinical parameters (SOFA score, vasopressor requirement, PaO₂/FiO₂ ratio) and inflammatory biomarkers (C-reactive protein, ferritin) before and after CytoSorb initiation.ResultsFollowing CytoSorb therapy, all four patients showed clinical improvement, evidenced by a reduction in SOFA scores, decreased vasopressor needs, and improved oxygenation. A concomitant decrease in inflammatory markers was also observed. All four patients survived and were discharged from the hospital in stable condition after an average ICU stay.ConclusionIn this small case series, adjunctive CytoSorb hemoadsorption was associated with rapid clinical stabilization and recovery in critically ill pregnant women with COVID-19, AKI, and hyperinflammation. These promising results warrant further investigation in controlled studies to confirm the efficacy and safety of this approach.